The clinical outcomes of total vs. half patellar tendon transposition combined with robot-assisted medial patellofemoral ligament reconstruction and extensive lateral release for the treatment of habitual patellar dislocation in adolescents - Liang, Qiuzhen; Zhan, Hongwei; Liu, Peidong; Zhang, Fujun; Zhao, Zandong; Kang, Xin; Liao, Chaofan; Tian, Bin; Zheng, Jiang; Zhang, Liang (Frontiers in Pediatrics, 2026)
PurposeThis study reviews a series of adolescent patients with habitual patellar dislocation (HPD) who underwent combined surgical procedures and compares the clinical outcomes between a total patellar tendon transposition group and a half transposition group.MethodsA retrospective cohort study of skeletally immature patients with HPD who underwent either total patellar tendon transposition or half patellar tendon transposition, in addition to robot-assisted MPFL reconstruction and extensive lateral release, between May 2018 and May 2023. The vertical distance between Schoettle's point and the medial distal femoral physis was measured intraoperatively using a navigation system. Clinical outcomes were evaluated through imaging studies, physical examinations, and pre- and postoperative functional ratings.ResultsA total of 58 patients were included in the final cohort. Among these, 30 patients were assigned to the total patellar tendon transposition group (TPTT group), while 28 patients were in the half patellar tendon transposition group (HPTT group). All patients returned for follow-up, at a mean of 31.5 ± 7.8 (range: 24–52) months after surgery. The average age of patients was 13.4 ± 1.7 (range: 11–16) years. The Schoettle's points were all located below the medial distal femoral physis, with a mean vertical distance of 5.88 ± 2.14 mm from Schoettle's points to the medial distal femoral physis. There was no recurrence of dislocation or severe complications; however, two patients (7.1%) in the HPTT group exhibited J sign. There was a statistically significant improvement in knee function scores among all patients (P < 0.001). At one-month postoperative assessment, the HPTT group demonstrated significantly higher Kujala scores compared to the TPTT group (P < 0.001). However, at final follow-up, the TPTT group showed superior functional outcomes, with higher Kujala (P = 0.033) and IKDC scores (P = 0.020) than the HPTT group. Compared with the preoperative results, there was a significant improvement in both the patellar tilt angle and the congruence angle (P < 0.001). No significant difference in the patellar tilt angle was observed between the two groups at the last follow-up (P = 0.730). Additionally, the congruence angle between the two groups showed a significant difference (P = 0.019) at the last follow-up.ConclusionsThe combined procedures, which include extensive lateral release, total patellar tendon transfer, and robot-assisted MPFL reconstruction, can achieve good patellar tracking and stability in the treatment of HPD in adolescents, and may provide better clinical outcomes than the half patellar tendon transposition group.